The water management issues of the socio-hydrosystem of Lake Guiers : conflicts and synergies of uses and users - (:unkn) unknown (My University, 2022)
The 2007-2008 food crisis put Food and Nutrition Security (FNS) back to the top of the African and international agendas. The many initiatives that followed took various approaches to increase productivity in order to improve FNS. Among these approaches, the international private sector's development was particularly put forward to fund and modernize African agricultures (Development 41455, 2008) to intensify agricultural production.(« Growing Africa , n.d.). Thus the implementation of these international agricultural businesses brings along deep changes on spatial and territorial organizations. According to many local actors, the implementation of these foreign businesses and its inherent agricultural development is nothing but a land grabbing and an exploitation of their ressources (Beuret & Cadoret, 2014). In Senegal, in St Louis and Louga regions, the Lake Guiers domain is one territory most concerned by the allocation of lands to foreign investors. Besides, the implementation of these international investors often leads to land use conflicts and requires a recomposition of these territories.Thus, our work emphasizes how the water management of the Lake Guiers limnic territory, as well as land ownership management, entail an attractivity of the private sector , even if it goes along with a shortening of the long-lived traditional practices and ancestral activities such as extensive farming, fishing, and rain agriculture . In addition, our study has enabled us to identify two different types of conflicts : internal conflicts (among the local actors themselves) and external conflicts (between the foreign investors and the local actors). Grounded on different scales, our analysis suggests a land recomposition not only based upon geographical proximity, hydraulic development, and the actors' technical and financial ressources, but also relying on sygergistic approaches to accept the implementation of foreign investors.
Keywords: African Research